Characteristics of Capoeta oguzelii, a new species of cyprinid fish from the Ezine Stream, Black Sea basin, Turkey (Teleostei: Cyprinidae) - Elp, Mahmut; Osmanoğlu, Mustafa İbrahim; Kadak, Ali Eslem; Turan, Davut (Informa UK Limited, 2018)
Four species of Capoeta (C. baliki, C. banarescui, C. sieboldii and C. ekmekciae) have been reported from Black Sea drainages, to date. We recognised an additional species in the Ezine Stream in the Southern Black Sea basin. Based on the analysis of 21 metric and 8 meristic data, we concluded that the Ezine Stream population forms a distinct, unnamed species, which we have described as Capoeta oguzelii sp. n. This species can be distinguished from all other Capoeta species by the following combination of characteristics: small size, presence of only one pair of barbels, absence of a keratinised edge of the lower jaw, a weakly ossified last simple dorsal fin ray, 7–10 gill rakers on the first gill arch and 7½ branched dorsal fin rays.http://www.zoobank.org/urn:lsid:zoobank.org:pub:066CC44A-3806-4DB7-8E88-AD971200E1EE
Keywords: 14. Life underwater